A Factor-Augmented Vector Autoregression Analysis of Business Cycle Synchronization in East Asia and Implications for a Regional Currency Union - Hyeon-seung Huh; David Kim; Won Joong Kim; Cyn-Young Park (Asian Development Bank (ADB), 2013)
Debate continues over whether a monetary or currency union will be a viable alternative to the current exchange arrangements in East Asia. This paper adds to the literature by assessing the level of business cycle synchronization among 10 major East Asian economies which is considered a key precondition for a regional currency union. Unlike previous studies, this paper employs a factor-augmented vector autoregression model that characterizes a large set of 62 foreign and domestic variables simultaneously. Five common shocks are identified, and we examine how and to what extent these shocks affect each economy in the region. Empirical results indicate that the majority of East Asian economies exhibit similar responses to world and regional shocks. Of particular importance is the finding that individual gross domestic products (GDPs) are well synchronized in response to the two major determinants of world and regional GDP shocks. Overall, the evidence presents positively for consideration of a regional currency union in East Asia. Some suggestions are offered concerning steps to build a foundation towards the establishment of an East Asian currency union.
hdl:11540/1985
Keywords: E32; F33; F44; 330; business cycle synchronization; Asian currency union; factor-augmented VAR